LIGNOCELLULOSES, SACCHARIDES AND BIO-ETHANOL YIELDS IN FUNGAL DI-CULTURE TREATED RICE HUSK - Stephen, Ezeonu Chukwuma (MATTER: International Journal of Science and Technology, 2016)
Pure monoculture strains of Aspergillus fumigates (AF), Aspergillus niger (AN), Aspergillus oryzae (AO), Trichophyton mentagrophyte (TM), Trichophyton rubrum (TR) and Trichophyton Sudanese (TS) were isolated from decomposing rice husk and di-culture combination in equal proportion used for treatment of fresh heat treated rice husk. Freshly processed rice husk in Mantle’s medium, were heat pre-treated using an autoclave at 121oC for 20 minutes. The isolated fungi di-culture combinations were inoculated into each of the pre-heated rice husk with the exception of two controls (heated rice husk C1 and untreated rice husk C2). Seven days rice husk fungal di-culture hydrolysis was followed by estimation of saccharine, lignocelluloses and bio-ethanol yields. Fungal did-culture treated rice husks were left to ferment for 7 days with introduction of both bakers’ and palm wine yeast. The result (in percent ± standard error of the mean) obtained in the work gave the highest carbohydrate (20.53 ± 1.39 %) from rice husks treated with TS + TR did-culture. Other highest values obtained were as follows: soluble reducing sugar percentage yield (2.54 ± 0.37 %) was obtained from AF + AN as well as AO + TR; soluble non reducing sugar (18.08 ± 1.10 %) was from TS + TR; total lignin percentage yield of 26.00 ± 2.06 % was from rice husk treated with AN+TR; cellulose yield of 66.00±0.96 and hemicelluloses yield of 32.50±1.78% were obtained from AN+TS and AO+TR fungal did-culture treated rice husks respectively. The introduction of yeasts from palm wine gave the highest bio-ethanol yield (14.18 ± 0.13 %) from TM + TR treated rice husk broth, while 6.56 ± 0.26 % of bio-ethanol was from AO + TS treated rice husk fermented with baker’s yeast. The selective treatment of rice husk with the fungal did-cultures illustrated to give the highest yield in each of the components carried out in this study will be ideal for the optimal production of the parameters studied from rice husk.